I don't think, I don't dream, I gaze! To prose works of Petr Borkovec - Lollok, Marek (Bohemica Olomucensia, 2023)
The paper explores the prose work of poet, novelist and cultural organiser Petr Borkovec, particularly his books Petříček Sellier & Petříček Bellot (2019) and Sebrat klacek (2020). Incorporating a number of excerpts, it presents the most distinctive features of Borkovec's prose style. Borkovec's prose works are characterized by fluctuations in genres, tensions between lyrical and epic principles, as well as between fiction and journalism. They usually deal with nature, travel, literature, or more generally comment on human life. Particular attention is paid to language and description as the author's most distinctive stylistic device.
Keywords: Petr Borkovec; contemporary Czech prose; short stories